Mobilization characteristics and strategies to improve hematopoietic progenitor cell mobilization and collection in patients with chronic granulomatous disease and severe combined immunodeficiency. Issue 2 (21st August 2014) - Panch, Sandhya R.; Yau, Yu Ying; Kang, Elizabeth M.; De Ravin, Suk See; Malech, Harry L.; Leitman, Susan F.
<x xml:space="preserve">Abstract</x> Background Granulocyte–colony‐stimulating factor (G‐CSF)‐mobilized autologous hematopoietic progenitor cells (HPCs) may be collected by apheresis of patients with chronic granulomatous disease (CGD) and severe combined immunodeficiency (SCID) for use in gene therapy trials. CD34+ cell mobilization has not been well characterized in such patients. Study Design and Methods We retrospectively evaluated CD34+ cell mobilization and collection in 73 consecutive CGD and SCID patients and in 99 age‐, weight‐, and G‐CSF dose–matched healthy allogeneic controls. Results In subjects aged not more than 20 years, Day 5 preapheresis circulating CD34+ counts were significantly lower in CGD and SCID patients than in controls; mean peak CD34+ cell counts were 58 × 106, 64 × 106, and 87 × 106/L, respectively (p = 0.01). The SCIDs had lower CD34+ collection efficiency than CGDs and controls; mean efficiencies were 40, 63, and 57%, respectively (p = 0.003). In subjects aged more than 20 years, the CGDs had significantly lower CD34+ cell mobilization than controls; mean peak CD34+ cell counts were 41 × 106 and 113 × 106/L, respectively (p < 0.0001). In a multivariate analysis, lower erythrocyte sedimentation rate (ESR) at mobilization was significantly correlated with better CD34+ cell mobilization (p = 0.007). In SCIDs, CD34 collection efficiency was positively correlated with higher red blood cell (RBC) indices (mean RBC volume, R2 = 0.77; mean corpuscular hemoglobin [Hb], R2 = 0.94; mean corpuscular Hb concentration, R2 = 0.7; p < 0.007) but not Hb. Conclusions CGD and SCID populations are characterized by significantly less robust CD34+ HPC mobilization than healthy controls. The presence of active inflammation or infection as suggested by an elevated ESR may negatively impact mobilization. Among SCIDs, markedly reduced CD34 collection efficiencies were related to iron deficiency, wherein decreased RBC size and density may impair apheresis cell separation mechanics.